2008
DOI: 10.1002/app.27607
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of blended polyimide and amine‐functionalized poly(orthosiloxane) composites

Abstract: Nanocomposite films were prepared through the blending of polyimide (PI) with octaphenyl silsesquioxane (OPS) and an amino-functionalized analogue, octaaminophenyl silsesquioxane (OAPS), with a solution-casting method. Although the PI-OPS composites showed visible phase separation at 5 wt %, the PI-OAPS composites were transparent with visible phase separation occurring only at 50 wt % OAPS. The interfacial interactions and homogeneity of the composites were characterized with scanning electron microscopy (SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…The effect of POSS is non-uniform ranging from strong deceleration to moderate acceleration of dynamics ( Figure 21). (MDA) polyimide [150]. A slight plasticization occurred due to increase of free volume, later confirmed by gas permeation experiments in [151].…”
Section: Blended Systems [Figure 21]mentioning
confidence: 61%
“…The effect of POSS is non-uniform ranging from strong deceleration to moderate acceleration of dynamics ( Figure 21). (MDA) polyimide [150]. A slight plasticization occurred due to increase of free volume, later confirmed by gas permeation experiments in [151].…”
Section: Blended Systems [Figure 21]mentioning
confidence: 61%
“…由于惰性取代基 POSS 与聚合物的 相容性较差, 分子之间并未形成共价键, 而反应性基团 可使其通过接枝或聚合反应与聚合物之间以化学键结 合在一起, 实现分子层次上的均匀分散. 近年来, 越来 越多的研究者倾向于合成和研究带有活性基团的 POSS 纳米分子 [4,5] . 2 结果讨论 …”
Section: 化 学 学 报unclassified
“…With the research available, it was shown that the addition of octaphenyl POSS (molecular silica) and octaaminophenyl POSS (multi-functional POSS) into polyimide matrix have led to the formation of phase separation with the former while exhibiting a homogenous morphology with the latter [27]. Another research showed that the addition of poly(ethylene glycol) (PEG) functionalized POSS (multi-functional POSS) in polymer intrinsic microporosity (PIMs) membrane had also led to the formation of phase separation [28].…”
Section: Introductionmentioning
confidence: 99%